TRAJECTORIES AND PREDICTORS OF STRAIN IN CAREGIVERS OF PERSONS WITH DEMENTIA: THE HERO PROGRAM. (11th November 2018) - Stratton, L; Margrett, J; Caskie, G; Shelley, M; Brown, L
Abstract: Sixty-five percent of caregivers report feeling their caregiving situation is moderately to highly stressful (National Alliance for Caregiving and AARP, 2015). The Health and Resilience Outreach (HERO) program provided telephone-based support and service referrals over time to 145 caregivers of people with dementia with an overall goal to decrease caregiver strain. Analyses examined change over time in caregiver strain and predictors of strain as assessed by the Modified Caregiver Strain Index. Latent growth analyses indicated caregivers significantly varied in initial levels of strain and that HERO was effective in preventing increased levels of caregiver distress that commonly occur in conjunction with the dementia disease process. Additional analyses revealed significant predictors of strain included initial level of strain, caregiver age, relationship type, and care recipient health behaviors (p < 0.05). Discussion focuses on individual and dyadic-level influences on strain as well as implications for program-level support on decreasing levels of strain.